DEVELOPING PUPILS`LISTENING COMPETENCE ON THE BASIS ON IELTS EXAMS - Mardonova Rano; Abdullaev Mashrab (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the significance of enhancing students' listening skills through the introduction of International English Language Testing System (IELTS) exam components in educational settings. Listening comprehension plays a vital role in language acquisition, enabling effective communication and understanding in various contexts. The IELTS exam, renowned for assessing English proficiency globally, offers a robust platform to elevate pupils' listening competence. By incorporating IELTS listening tasks, learners engage with authentic audio materials, diverse accents, and complex speech patterns akin to real-world scenarios. This integration not only enhances students' academic preparedness but also fosters cultural awareness and critical listening abilities. Through a focus on IELTS-based listening practice, educators can empower pupils to navigate linguistic challenges confidently, equipping them with essential skills for success in academic and professional environments.